Organizing Global Marketing - ARAFA, AHMED (Dirasat in Economics and Business, 1981)
The purpose of this article is to outline the main approaches utlized for organizing global marketing, and to propose an integrated model that can be helpful in this concern. The model presents three approaches for organizing global marketing, indicanting circumstances and conditions for applying each approach, problems that may accompany each one, and ways to avoid these problems. The main purpose of presentig this (three dimentional)) model is to contribute to knowledge by providing a theoretical base for increasing global marketing performance.